Ventajas competitivas de la importación de materias primas textiles en Colombia en los últimos 10 años (2020)
This research was made for a better understanding of the competitive advantages of importing textile raw materials in Colombia from the last 10 years, going through an analysis of 2 textile companies to Colombia, which provides much of the information described through a virtual interview. Likewise, it is possible to find a relationship and a connection point between the Colombian textile raw materials such as: cotton, wool, linen, etc. and national imports from countries like United States and South Korea, finishing with competitive advantages such as productivity, quality and innovation that our country could have respecting other international competitors.